2020
DOI: 10.21203/rs.2.12941/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social acceptance of alcohol use in Uganda

Abstract: Background: Alcohol use is part of many cultural, religious and social practices, and provides perceived pleasure to many users. In many societies, alcoholic beverages are a routine part of the social landscape for many in the population. Relatively low rates were reported for Alcohol Use Disorders (AUD) in a community based survey and facility detection survey conducted in the study site contrary to findings in earlier formative studies where alcohol use was reported to be a major health problem. The aim of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Often, they would offer alcohol to their children, or the children would steal the alcohol [4]. Another study from Uganda showed how some parents administered alcohol to children as medicine, with a belief that it cures cough, flu, malaria and kills intestinal germs [25]. Parents could proudly introduce their children to alcohol, especially the boys, and were happy to have their sons drink, just like them.…”
Section: Major Findingsmentioning
confidence: 99%
“…Often, they would offer alcohol to their children, or the children would steal the alcohol [4]. Another study from Uganda showed how some parents administered alcohol to children as medicine, with a belief that it cures cough, flu, malaria and kills intestinal germs [25]. Parents could proudly introduce their children to alcohol, especially the boys, and were happy to have their sons drink, just like them.…”
Section: Major Findingsmentioning
confidence: 99%